A normative analysis of the 2025 budget realization report presentation based on government accounting standards in indonesia - Doni Wirshandono Yogivaria (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to analyze the presentation of the 2025 Budget Realization Report (BRR) in Indonesia based on Government Accounting Standards (SAP) using a normative perspective. The research employs a qualitative approach with a literature study (library research) design, relying on secondary data derived from government regulations, academic literature, and relevant official documents. The data were collected through documentation techniques and analyzed using qualitative content analysis to assess the conformity of the BRR presentation with established accounting standards. The findings indicate that the presentation of the BRR demonstrates a high level of structural compliance with SAP, particularly in terms of format, classification, and the inclusion of key financial components such as budget allocation, realization, and variance. However, the study also reveals that substantive aspects, including transparency, completeness of disclosure, and interpretability, remain at a moderate level. The report tends to emphasize formal compliance rather than effective communication, as evidenced by limited explanatory narratives and insufficient variance analysis. These limitations reduce the usefulness of the BRR as an instrument of public accountability and financial transparency. In conclusion, while the BRR fulfills its formal role in financial reporting, improvements are needed to enhance its communicative function and overall quality. This study contributes to the literature by providing a normative evaluation of public sector financial reporting and offers insights for improving accountability and governance practices in Indonesia.